The Reforms of Umar ibn Abd al-Aziz in the Umayyad Caliphate - Muqoddam Cholil; Ahmad Faris (Yayasan Darussalam Bengkulu, 2026)
After approximately four decades of Umayyad rule, several political, administrative, and moral problems emerged within the caliphate. Some rulers were perceived as moving away from the ethical foundations of Islamic governance, creating injustice, nepotism, and social tension. This article describes the reforms of Caliph Umar bin Abdul Aziz within the Umayyad government by strengthening the original manuscript through a qualitative library research design, historical-content analysis, and recent secondary literature. The revised analysis shows that Umar bin Abdul Aziz’s reform was not merely moral advice, but a structured governance agenda: protecting the weak, correcting nepotism, replacing unjust governors, restoring public assets to the Bayt al-Mal, strengthening accountable administration, and directing power toward public welfare. Although his reign was brief, the reform model remains relevant for discussions on clean government, social justice, bureaucratic reform, and ethical leadership.